Estimation of the Eyeball and Orbital Volume Using the Cavalieri Principle on Computed Tomography Images - Acer, Niyazi; Demir, Mehmet; Ucar, Tolga; Pekmez, Hidir; Goktas, Atilla (Galenos Publ House, 2011)
Objective: The volumes of the eyeball and orbit have been the subject of a few studies, yet none of them have used stereological methods to estimate the volume. In the present study, we estimated the volumes of the eyeball and orbits in normal healthy men and women using the stereological method. Material and Methods: We estimated the volume of the eyeball WE) and the volume of the orbit (VO) in normal men and women using the Cavalieri principle as a combination of a point-counting technique. We used computed tomography scans taken from 31 subjects (12 men and 19 women). Results: The mean (+/- SD) VO in the female subjects was 18.47 +/- 2.52 cm(3) on the right side and 18.16 +/- 2.52 cm(3) on the left side. The VE was 7.45 +/- 1.19 cm(3) and 7.45 +/- 1.25 cm(3) on the right and left sides, respectively. The mean (+/- SD) VO in the male subjects was 22.35 +/- 3.05 cm(3) on the right side and 22.71 +/- 2.80 cm(3) on the left side. The VE was 7.32 +/- 0.74 cm(3) and 7.61 +/- 1.04 cm(3) on the right and left sides, respectively. Conclusion: Measurement by the technique described is an easy, and quick method of assessing the volumes of the eyeball and orbit.
Keywords: Tomography computed; orbit; eye; anatomy; stereology; cavalieri principle